Macro-infaunal diversity and assemblage in the mangrove habitat of Lawas, Sarawak, Malaysia - Abdulla-Al-Asif; Hamli, Hadi; Idris, Mohd Hanafi; Gerusu, Geoffery James; Ng, Ji Feng; Kamal, Abu Hena Mustafa (Elsevier BV, 2023)
The diversity and composition of macrofaunal communities are important components to understand the mangrove ecosystem structures and functions. To understand the seasonal distribution of macro-infaunal community and diversity, this study was conducted from July 2019 to February 2020 in the intertidal mangrove forest of Punang-Sari-River estuary, Lawas, Sarawak. Sampling was carried out during post-monsoon, intermediate-September, pre-monsoon, and monsoon. It was observed that, the seasonal physico-chemical parameters were significantly (P < 0.05) different, including the temperature, salinity, rainfall, pore water nitrogenous compounds (NO2, NO3 and NH3-N), phosphate and micro minerals. A total of 39 infaunal macrobenthos taxa from 27 families were recorded while the mean abundance of infaunal macro benthos was found higher in monsoon (997.29 individuals/m2). The most abundant, the highest important species index and percentage contribution species was Bivalvia Eurytellina lineata (W. Turton, 1819) due to year-round favorable ecological condition. Seasonal faunal grouping suggested post-monsoon, intermediate-September and pre-monsoon were comparable in species and individual abundance. The Simpson, and Shannon indices were found significantly (P < 0.0001) higher in monsoon, while Margalef richness was found higher in pre-monsoon. The soil was sandy loam with major portion of sand, and positively correlated with sand and infaunal abundance in all seasons. The ANOSIM and SIMPER analysis suggested that the highest species abundance similarity was observed between post-monsoon and pre-monsoon, while the highest dissimilarity was observed between intermediate-September and pre-monsoon. The Canonical Correspondence Analysis results suggested, a number of species were influenced by ecological factors, for instance, salinity, soil pH, PO4, micro–macro minerals, water pH, and nitrogenous compounds. The relationship within benthic infaunal abundance in the mangrove ecosystem with their seasonality, ecological variables, and soil properties were established and addressed in this study.